2017
DOI: 10.1371/journal.pone.0170705
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Variation of the Incidence Rate of Lower Limb Amputation in Australia from 2007-12

Abstract: In Australia, little is known about how the incidence rate (IR) of lower limb amputation (LLA) varies across the country. While studies in other economically developed countries have shown considerable geographic variation in the IR-LLA, mostly these have not considered whether the effect of common risk factors are the same across regions. Mapping variation of the IR-LLA, and the effect of common risk factors, is an important first step to focus research into areas of greatest need and support the development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
51
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(62 citation statements)
references
References 23 publications
10
51
0
1
Order By: Relevance
“…The mean age at LEA in our study was 57 years, about 10 years younger than that reported in other developed countries . Indigenous patients were even younger at 52.9 years, compared to the Australian national average age at LEA of 62.9 years . This is in accordance with a previous study from Far North Queensland .…”
Section: Discussionsupporting
confidence: 89%
“…The mean age at LEA in our study was 57 years, about 10 years younger than that reported in other developed countries . Indigenous patients were even younger at 52.9 years, compared to the Australian national average age at LEA of 62.9 years . This is in accordance with a previous study from Far North Queensland .…”
Section: Discussionsupporting
confidence: 89%
“…The rates of BKA in this study as a proportion of total MLLAs (62.7%) was comparable to other Australian cohorts, with Lim et al . reporting 58.6% and a study looking at 5 years’ worth of data from all Australian states reporting 57.3% . This study found that Indigenous patients were significantly more likely to undergo BKA as opposed to above knee amputation, and one hypothesis for this could be due to sepsis being a more common indication, necessitating immediate definitive intervention.…”
Section: Discussionsupporting
confidence: 77%
“…Lower limb amputations, particularly in the context of diabetes, have been used as an indicator internationally to compare different health systems performance . Both Australian and international reports have shown that there are geographical variations in the incidence of MLLAs within nations . The most comprehensive report looking at geographical variation within Australia suggested further research to be focused on smaller geographical regions to determine specific at‐risk populations for lower limb amputations …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations